The role of the church in motivating entrepreneurship to improve the economy of indigenous peoples in Papua, Indonesia - I Wayan Ruspendi Junaedi; Dermawan Waruwu; I Wayan Damayana; I Gusti Bagus Rai Utama (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
The novelty of this research proves that the tarekat has not been able to encourage and motivate the growth of entrepreneurship to improve the economy of indigenous peoples in Papua. The purpose of this study is to analyze the challenges faced by GKI in Papua to improve the economy of indigenous peoples in the face of the dynamics of a rapidly changing world to improve the economy of the Papuan people. This research was conducted in depth using qualitative descriptive methods in Papua with in-depth interviews, observation, and secondary data techniques. The results show that the efforts of the Indonesian Christian Church in Papua in improving the economy of indigenous peoples are still minimal, both at the synod, classical and congregational levels. The congregation is currently experiencing severe challenges both internally and externally. They have been struggling with the global Covid-19 pandemic situation. Many areas in Papua are still having problems with the internet network which makes communication even more difficult. To improve the economy of indigenous peoples, the congregation tries to implement the necessary traditional empowerment strategies and strategic steps, namely open heart-to-heart dialogue by all church components internally at various levels.